Hereford cattle - Miller, Fred Carl (My University, 1907)
Introduction: The major object in raising cattle is for profit, and their final destiny is the block, so let us consider the breed that will come nearest meeting those requirements. In taking up Herefords let us take a glimpse of their origin. That they are an old English breed is probably true. McDonald and Sinclair in their famous history of Hereford cattle state; "The Herefords are originally a self coloured race of cattle like the Devons and Sussex and that they were derived from the same source." Marshall who saw the breed on its native pastures in 1788, described the color as "a middle red with a bald face," the last being esteemed characteristic of the true Hereford breed. One of the first efforts to assign to a specific cause the the superior quality and characteristic color of the Hereford breed was made by Mr. Thos. Knight, who asserts that Lord Scudmore introduced into the county of Hereford from Flanders, a number of red cattle with white faces prior to 1670 and that they attributed superior qualties to the breed. That they were of good class ere this is proven by John Speed a noted agriculturist (editor) in 1627, when he mentiones the excellent condition of the cattle in Herefordshire, England. It is also thought by some that the white cattle of Wales had been crossed with the native breed as their prevalence in the adjoining county of Brecknock has been satisfactorily established. If such is the case, it is almost a certainty that they were the cause of the appearance of animals with white markings which doubtless assisted the early improvers in fixing a white face as a dominant characteristic.
Citation: Miller, Fred Carl. Hereford cattle. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Hereford Cattle; Cattle; Live Stock; Heredity; Theses